Poverty and Sustainable Socio-Economic Development in Africa: The Nigerian Experience - Justine, Igbokwe-Ibeto Chinyeaka; Ighodalo, Akhakpe; Okpo, Oteh Chukwuemeka (Asian Economic and Financial Review, 2012)
There has been a growing incidence of poverty in sub-Saharan Africa over the last two decades. Poverty is a multidimensional social phenomenon that can be analytically divided into two main perspectives: human poverty which is the lack of human capabilities and income poverty, which is the lack of income necessary to satisfy basic need e.g. poor life expectancy, poor maternal health, illiteracy, poor nutritional levels, poor access to safe drinking water and perceptions of well-being. The paper examines several initiatives focused on poverty eradication that Nigeria have adopted through national actions to fight both human and income poverty. In analysizing the issues raised, we anchored the paper on an eclectic approach of radical, Marxist model of political economy and the social exclusion theories. The study established among others, that a lot of effort has been made in poverty reduction through poverty alleviation programs in Nigeria. However, it is of knowledge that in spite of the previous efforts of various governments to alleviate poverty in Nigeria and the efforts of the current government to effect same, nothing much had changed in the living conditions and standards of the people. Poverty is still growing at an alarming rate. The challenges of poverty alleviation strategies in the Nigerian situation were articulated in the context of sustainable socio-economic development and the paper concludes that poverty alleviation in contemporary Nigeria require both socio-economic policies geared towards sustainable development. However, to enhance the human capital of the poor in particular, priorities for educational reforms should be in the areas of basic education, vocational training, water and sanitation, health care delivery, agriculture and housing for all. It is the position of this paper that until African leaders in general and Nigeria in particular begin to think ‘We’ and not ‘I’, the fight against poverty that could engender sustainable socio-economic development will for long remain a mirage.